Explanations of the tentative new physics anomalies and dark matter in the Simple Extension of the Standard Model (SESM) - Tianjun Li; Junle Pei; Xiangwei Yin; Bin Zhu (Nuclear Physics B, 2024)
We revisit the Simple Extension of the Standard Model (SESM), which can account for various tentative new physics anomalies and dark matter. The B physics anomalies, muon anomalous magnetic moment, and dark matter can be explained already in SESM. In this work, we study the unitarity constraint on this model and comment the parameter space on the edge of unitarity bounds. Besides, the complete scalar potential is considered which is needed to address the W boson anomaly and more dark matter (co-)annihilation processes are discussed. We perform a systematic study, and find the viable parameter space which can explain these anomalies and evade all the current experimental constraints.